2016
DOI: 10.1249/jsr.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Overuse Injuries in the Pediatric Population

Abstract: In pediatric patients, musculoskeletal overuse injuries are common clinical complaints. Recently, the number of youth who are engaged in formal competition has increased. A National Council of Youth Sports survey found that 60 million children aged 6 to 18 yr participate in some form of organized athletics. Surveillance reporting systems, such as the National High School Sports-Related Injury Surveillance System and the High School Reporting Information Online (high school RIO), an Internet-based sports injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…Navicular stress fractures have been reported in children, but account for only 4% of all childhood stress fractures (13). Recent articles, including a review of overuse injuries in the pediatric population, reported on several stress fractures, but none were of the navicular (14,15). A case of a navicular stress fracture from overload because of an equinus gait has been reported in a similarly aged female with cerebral palsy (2).…”
Section: Discussionmentioning
confidence: 99%
“…Navicular stress fractures have been reported in children, but account for only 4% of all childhood stress fractures (13). Recent articles, including a review of overuse injuries in the pediatric population, reported on several stress fractures, but none were of the navicular (14,15). A case of a navicular stress fracture from overload because of an equinus gait has been reported in a similarly aged female with cerebral palsy (2).…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Conservative treatment includes the rest from weight-bearing exercise, bracing of the wrist, and physiotherapy. [ 11 ] Without early recognition and treatment, repetitive injury causes early closure of the physis, and it can lead to growth arrest, instability, and chronic pain. [ 1 , 7 ] In this case, the patient had repeated fractures, but the sites of fractures were different.…”
Section: Discussionmentioning
confidence: 99%
“…Ao se analisar o panorama das alterações ortopédicas da infância, pode-se notar a importância da atenção dos pediatras para sua ocorrência e devida referência ao médico especializado ou resolução na atenção primária em quadros temporários ou fisiológicos, bem como a constante atualização destes profissionais para e realização de corretos diagnósticos e tratamento 3,4 . Deve-se ainda ressaltar a relevância da dedicação dos ortopedistas em razão da fase de transição da infância para a vida adulta ser bastante diferenciada quanto às patologias e manejo do trauma [4][5][6][7][8] .…”
Section: Introductionunclassified